Reliability and reproducibility of perfusion MRI in cognitively normal subjects - Jiang, Li (2010)
Arterial spin labeling (ASL) MRI is becoming a popular method for measuring perfusion due to its ability of generating perfusion maps non-invasively. This allows for frequent repeat scanning, which is especially useful for follow-up studies. However, limited information is available regarding the reliability and reproducibility of ASL perfusion measurements. Here, the reliability and reproducibility of pulsed ASL (PASL) was investigated in an elderly population to determine the variation in perfusion among cognitively normal individuals in different brain structures. Intra-class correlation coefficients (ICC) and within-subject variation coefficients (wsCV) were used to estimate reliability and reproducibility over a period of one year. Twelve cognitively normal subjects (75.5±5.3 years old, six male and six female) were scanned four times (at 0, 3, 6 and 12 months). No significant difference in cerebral blood flow (CBF) was found over this period. CBF values ranged from 46–53 ml/100g/min in the medial frontal gyrus (MFG) and from 40–44 ml/100g/min over all gray matter regions in the superior part of the brain. Data obtained from the first two scans were processed by two readers and showed high reliability (ICC>0.97) and reproducibility (wsCV <6%). However, over the total period of one year, reliability reduced to a moderate level (ICC = 0.63–0.74) with wsCVs of gray matter, left MFG, right MFG of13.5%, 12.3% , and 15.4%, respectively. In conclusion, measurement of CBF with pulsed ASL provided good agreement between inter-raters. A moderate level of reliability was obtained over a one-year period, which was attributed to variance in slice positioning and coregistration. As such pulsed ASL has the potential to be used for CBF comparison in longitudinal studies.